Six Fractal Codes of Biological Life Unifying ATOMS, WAVES and INFORMATION: Perspectives in Exobiology, Cancers Basic Research and Artificial Intelligence Biomimetism Decisions Making - Perez, Jean-claude (Journal of Medical Informatics and Decision Making, 2021)
In this theoretical discovery of a law of Life, there is MATHEMATICS (Geometry, Bits and Numbers) that UNIFY 3 universes as complementary as ATOMIC MASS, WAVES, and INFORMATION (DNA, RNA and Amino Acids). The discovery of a simple numerical formula for the projection of all the atomic mass of life-sustaining CONHSP bioatoms leads to the emergence of a set of Nested CODES unifying all the biological, genetic and genomic components by unifying them from bioatoms up to 'to whole genomes. In particular, we demonstrate the existence of a digital meta-code common to the three languages ​​of biology that are RNA, DNA and amino acid sequences. Through this meta-code, genomic and proteomic images appear almost analogous and correlated. The analysis of the textures of these images then reveals a binary code as well as an undulatory code whose analysis on the human genome makes it possible to predict the alternating bands constituting the cariotypes of the chromosomes. The application of these codes to perspectives in astrobiology, cancer, and specifically in INFORMATION THEORY with the emergence of binary codes and regions of local stability (voting process), whose fractal nature we demonstrate, is illustrated. PREFACE by Professor Luc Montagnier Addendum by Robert Friedman M.D After the discovery of the DNA double helix structure allowing both the stable storage of genetic information and its transfer through messenger RNA to protein synthesis organelles themselves structured by RNA most abundant in cells, the ribosomal. This wonder of nature exists in ALL living beings from the virus to humans and is based on two codes, the linear sequence of nucleotides and that derived from codons where three nucleotides allow with a certain flexibility - synonymous codons - the choice in the twenty amino acids. But we are missing a third CODE the one governing at multicellular beings from the rotifer to human, the stabilized modulation of gene expression in a nutshell the differentiation of cells from the single cell of the fertilized egg. It is logical to think that this program which begins as soon as fertilization is written in the DNA. We are also prone to associate it with non-coding DNA sequences although they control gene expression. I introduce here the notion developed by Jean-Claude Pérez of mathematical harmony, a higher order present in all living beings and whose existence it finds in genomes, including those of viruses. Thus the natural evolution of variants of the genome of coronavirus Covid 19 tends towards increasingly long Fibonacci series. It remains to determine the Who, the How and the Why of such developments. I will bet with my mathematician colleague that waves and fractals play a role. Luc Montagnier ADDENDUM Jean-claude has given scientists a strong new direction for research. He has identified a unified field of science guided by the Golden Ratio and Fibonacci Sequence. By identifying an overall guiding principle that makes possible fractal-like nesting at all levels of biological manifestation, future researchers can begin with the "whole" instead of the "parts". If we know that complex systems are organized at varying levels by the Golden Ratio and Fibonacci Sequence, we can look for those universal patterns first and then fill in the gaps with small details to complete the picture. It's like having an overall view of a crossword puzzle before beginning to assemble the individual pieces. Without an overarching vision and guiding principle, completing the puzzle is infinitely more difficult. Once scientists and researchers realize and begin using this "SECRET IN HIDDEN IN PLAIN SIGHT," their discoveries will be orders of magnitude more fruitful.  Robert Friedman M.D
Keywords: Fractal Codes; Exobiology; Cancer; DNA; Human Genome